Enhanced Programmed Death 1 and Diminished Programmed Death Ligand 1 Up‐Regulation Capacity of Post‐Activated Lupus B Cells. Issue 9 (6th August 2019) - Stefanski, Ana‐Luisa; Wiedemann, Annika; Reiter, Karin; Hiepe, Falk; Lino, Andreia C.; Dörner, Thomas
Abstract : Objective: To assess the expression of programmed death 1 (PD‐1), PD ligand 1 (PD‐L1), and PD‐L2 by B cells from patients with systemic lupus erythematosus (SLE) at baseline and after in vitro stimulation and to analyze their functional relationship to B cell proliferation. Methods: Peripheral blood mononuclear cells obtained from 29 SLE patients and 27 healthy donors were stimulated with interleukin‐2 (IL‐2)/IL‐10, anti–B cell receptor (anti‐BCR), CpG, and CD40L alone or in combination. Expression of PD‐1, PD‐L1, and PD‐L2 on defined B cell subsets as well as on CD3+ T cells was analyzed by flow cytometry at baseline and after 48 hours of stimulation. Additionally, after 48 hours of stimulation, CD71 was evaluated as a proliferation marker on CD19+CD20+ B cells. Results: Increased PD‐1 expression was characteristic of unstimulated lupus B cells and T cells. Upon stimulation of B cells with IL‐2/IL‐10, anti‐BCR, CpG, and CD40L for 48 hours, the capacity of SLE B cells to up‐regulate PD‐L1 expression was substantially diminished ( P = 0.0006) along with reduced B cell proliferation ( P = 0.0039). Reduced PD‐L1 expression was inversely correlated with the presence of the interferon signature (r = –0.8571, P < 0.0001) and the clinical SLE Disease Activity Index score (r = –0.5696, P = 0.0087). Conclusion: Post‐activated, hyporesponsive lupus B cells are characterized by a phenotype of increased PD‐1, functionally diminished PD‐L1 up‐regulation capacity, and reduced proliferation upon stimulation.